Tuberculous Uveitis as an Extrapulmonary Manifestation of TB: Diagnostic and Therapeutic Challenges - Widhyasti, Rahayu; Pamungkas, Seno; Anggraini, Susan (Syntax Corporation, 2025)
Tuberculosis (TB) continues to pose a global health challenge, particularly in tropical and developing regions. Although primarily a pulmonary disease, TB can manifest in extrapulmonary forms, including ocular involvement such as uveitis. This study aims to describe the diagnostic and therapeutic challenges associated with tuberculous uveitis in a young female patient previously diagnosed with pulmonary TB. The patient presented with rapid progressive vision loss in one eye and was later diagnosed with uveitic tuberculosis. Despite receiving standard anti-tubercular therapy (ATT) and corticosteroids, irreversible retinal damage led to permanent vision loss. The research employs a case report approach with clinical evaluations including slit lamp, ultrasonography, and fundus examinations. Findings underscore the diagnostic difficulty due to nonspecific ocular symptoms and the often presumptive nature of ocular TB diagnosis, lacking microbiological confirmation. Early treatment improved inflammation but failed to restore vision. This case highlights the necessity of integrating ophthalmic evaluations into TB management, especially in endemic regions. Multidisciplinary collaboration among healthcare providers is vital for effective diagnosis and timely treatment. The study emphasizes the importance of routine ocular screening in systemic TB cases and calls for further research into early diagnostic biomarkers and treatment guidelines to prevent vision loss in similar patients.